The therapeutic effect of Taijiquan combined with acupoint pressing on the treatment of anxiety insomnia in college students: A study protocol for a randomized controlled trial - Deng, Jianya; Liu, Xinyan; Wang, Yiming; Fan, Jieyang; Yang, Li; Duan, Jiamin; Yuan, Yongfang; Lan, Peishu; Shan, Zhuoxuan; Xiong, Junfeng; Peng, Wenyu; He, Qingfeng; et al. (Frontiers in Psychiatry, 2022)
Sleep health is an important part of health and has become a common concern of society.For anxiety insomnia, the commonly used clinical therapies have limitations. Alternative and complementary therapy is gradually rising and showing remarkable effect in clinical practice.This is the first study to evaluate the therapeutic effect of Taijiquan combined with acupoint pressing in the treatment of anxiety insomnia in college students, and to compare the difference of intervention before and after sleep, in order to choose the best treatment time.